Study on Gas Migration Law of Mining Coal Seam under the Influence of Normal Fault - Xiangtao Kang; Meng Tang; Mingquan Jiang; Cunliu Zhou; Jinguo Hu; Jiachi Ren; Bozhi Deng (Geofluids)
In order to study the coupling law of mining and gas migration in close coal seams in fault structure area, taking the coal mining face in Guizhou as the research background, the development of mining fracture field and gas migration law of No. 5 coal seam and No. 9 coal seam were studied. Based on the development of mining-induced fracture field in coal seam, the fracture distribution was binarized and quantitatively analyzed by using fractal dimension, and the gas migration law of mining-induced fractures in No. 5 coal seam and No. 9 coal seam was simulated and studied. The results show that under the condition of U-shaped ventilation, the gas accumulates seriously in the upper corner of the mining fracture field, and the gas generally floats and accumulates to the separated layer development area of the overlying strata. Due to the existence of faults, even if the mining-induced fracture field in goaf of No. 9 coal seam is within the mining-induced pressure relief range of No. 5 coal seam, the gas concentration in the mining-induced fracture field is still high, and the variation gradient of gas concentration is large. The gas will circulate actively and accumulate easily near the fault structure, and the gas concentration at the high level of the fault is slightly higher than that at the low level. The research results can provide some reference for the mining of close coal seams in the fault structure area, the comprehensive prevention and control of gas, and the safe and efficient production of coal mines.